Applying the Contextual Teaching and Learning Model to Enhance 21st Century Skills in Fikih Learning: A Case Study in Madrasah Aliyah - Milda Muliati; Silfia Hanani; Zulfani Sesmiarni; Supratman Zakir; Iswantir M (AL-ISHLAH: Jurnal Pendidikan, 2025)
The limited application of varied, contextual teaching methods in Fikih learning has led to a gap in students' ability to connect religious concepts with real-life situations, limiting the development of 21st-century skills. This study investigates the implementation of the Contextual Teaching and Learning (CTL) model in Fikih education at Madrasah Aliyah and its effectiveness in enhancing students’ critical thinking, creativity, collaboration, and communication skills. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with a principal, one Fikih teacher, and students, as well as document analysis. Data were analyzed using thematic coding and triangulation to ensure validity. Findings reveal that CTL was implemented through key stages including constructivism, inquiry, questioning, learning communities, modeling, reflection, and authentic assessment. Students showed improved engagement, deeper understanding of Fikih concepts, and increased ability to relate them to contemporary social issues. Challenges identified include varying student abilities and time constraints, which were addressed through differentiated instruction, teacher creativity, and stakeholder collaboration. The study concludes that CTL is an effective pedagogical model for Islamic education, particularly in fostering 21st-century competencies in Fikih learning. It highlights the need for continuous professional development for teachers, integration of authentic assessments, and the use of real-life contexts in religious instruction. Broader implementation of CTL is recommended to support holistic student development in Madrasah environments.